QUALITY OF FINANCIAL REPORTS IN PAPUA PROVINCE: WHAT FACTORS INFLUENCE IT? - Wulan Asmiati; Sahrul Ponto; Dian Pertiwi; Fajar Rina Sejati (Applied Accounting and Management Review (AAMAR), 2023)
Government accounting standards, internal control systems, regional government financial accounting systems, and resource competencies were tested to see whether they had an effect or not on the quality of local government financial reports in Papua Province. A total of 57 questionnaires from 27 OPDs were analyzed using multiple linear regression analysis. The results of this research indicate that government accounting standards and human resource competency respectively have an influence on the quality of local government financial reports. In other hand, internal control system and regional government financial accounting system respectively has no effect on the quality of regional government financial reports. It is hoped that the implications of this research can be input for the government of Papua Province to improve the quality of its financial reports.